Pré-melhoramento genético, floração in vitro e criopreservação de orquídeas nativas do cerrado - Carneiro, Luciano Lajovic (2014)
The vast majority of orchids species are pollinated by insects, mainly bees, butterflies and moths. The orchid family is generally considered allogamic, but information about the type of reproduction are unknown for most species. Little information exist about orchids of Cerrado, which hinders plant breeding of these species and postpones their use in developing new varieties for the ornamental market. Recent methods of plant biotechnology can assist both plant breeding and conservation of these species, such as induction of early in vitro flowering as important technique particularly for species with a long cycle, and cryopreservation as a tool for the conservation of genetic variability. This study aims to contribute to the improvement and conservation of orchids with distribution in the Brazilian Cerrado. Selfcompatibility was evaluated for seven species: Cohniella cepula, Cyrtopodium eugenii, C. saintlegerianum, Epidendrum densiflorum, Epidendrum nocturnum, Epidendrum secundum e Lockhartia goyazensis. Only three were autocompatible: Epidendrum nocturnum, Epidendrum secundum and Lockhartia goyazensis. Interspecific compatibility was assessed for Cyrtopodium and Epidendrum genera, using reciprocal crosses. Just E. nocturnum and C. eugenii produced viable seeds. For early in vitro floral induction 20 different treatments were used through nutritional changes and use of cytokinin (BAP) in modified MS medium. Only C. cepula showed positive responses to treatment with formation of 46% floral stems. The effect of BAP was evident in the results. Cryopreservation was tested by vitrification of seeds of seven species of orchids, obtained from outcrossing. The responses to cryopreservation were partially different for each species. Most seeds tested showed any significant differences between freezing in liquid nitrogen without cryoprotectants and control without freezing. The freezing without cryoprotectant was successful to maintaining seed viability for all species, C. cepula 63%, C. eugenii 59%, C. sainttlegerianum 70%, E. densiflorum 42%, E. nocturnum 31%, E. secundum 69% and L. goyazensis 52%. Only E .nocturnum and C. cepula showed a significant reduction in viability when submitted to freezing in liquid nitrogen. The results presented here are useful for the development of breeding programs for orchids and conservation of these species.